FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY: - VARIANADA HALIM (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2000)
The requirement that annual financial statements be subjected to external audit can conflict with the requirement of timely reporting. To the extent that auditing is a time from a company's fiscal year-end to the date of the auditor's report. Audit delay can affect the timeless of accounting information releases, and it is well known that timeliness is associated with the market's reaction to the information released. Therefore, research on the determinants of audit delay may improve our understanding and contribution to control these factors more efficently and effectively. A prior, it appears that several variables are relevant to audit delay. This study designs seven variables as investigation objects to explain factors/determinants that affects audit delay. The results can be interpreted that audit delays tend to be longer for the company that announces loss, applies December 31 as fiscal year-end and has a longer relationship to the audit firm.